Pengaruh Pendidikan Karakter dan Disiplin Belajar Terhadap Hasil Belajar Siswa Setingkat SD (Indo-MathEdu Intellectuals Journal, 2025)
Character education is one of the strategic approaches to shaping students' attitudes, values, and morals, while learning discipline plays an important role in creating consistent and structured learning habits. This research aims to analyze the influence of character education and learning discipline on student learning outcomes at the elementary school level. The method used in this study is a literature review by analyzing various relevant previous research sources. Data analysis is carried out by identifying, classifying, and evaluating findings related to character education, learning discipline, and student learning outcomes, which are then synthesized into a conclusion. The results of the study show that character education has a positive impact on the formation of positive attitudes in students, such as responsibility, honesty, and cooperation, which directly supports the improvement of learning outcomes. Learning discipline has also been proven to enhance concentration, time management, and student motivation in learning. The combination of effective character education and good learning discipline significantly contributes to achieving optimal learning outcomes. This research suggests the importance of integrating character education into the curriculum as well as habituating learning discipline from an early age to support the success of student learning at the elementary school level